Development of Skills in The Preparation of Music Art Modules "Nyong Wong Tegal" Based on Experiental Learning in Merdeka Belajar Concept for Elementary School Teachers in Tegal Regency - Andaryani, Eka Titi; Armaidi, Indriana Eko; Wantoro, Wantoro; Widjanarko, Paulus (Jurnal Abdimas, 2024)
The Nyong Wong Tegal Music Art Module based on Experiental Learning is a new breakthrough in the world of music education in Indonesia which is in accordance with the concept of Merdeka Belajar. The purpose of this service is to assist in the preparation of music art modules that contain the culture of Tegalan songs based on Experiental Learning for elementary school teachers in Tegal Regency. The methods used are lectures, discussions, practices, simulations, and evaluations. The results of this service include: (1) The Nyong Wong Tegal Music Art Module based on Experiental Learning assists teachers in learning music art in the classroom; (2) elementary school teachers are given proper practice of Tegalan song singing techniques; (3) Elementary school teachers are given practical assistance in implementing the Nyong Wong Tegal module in the classroom.